THE INFLUENCE OF NAZHIR HUMAN RESOURCE CAPACITY ON THE EFFECTIVENESS OF PRODUCTIVE WAQF LAND MANAGEMENT IN SEPEMPANG VILLAGE - Natuna Adi Putra Natuna; Umar Natuna; Kartubi (SOSIOEDUKASI, 2026)
This study aims to examine the influence of nazhir human resource capacity on the effectiveness of productive waqf land management in Sepempang Village and to identify which capacity dimension carries the most dominant contribution. A quantitative explanatory approach was employed, with data collected through a structured Likert-scale questionnaire administered to nazhir members and relevant stakeholders using a total sampling technique. Data analysis utilized simple linear regression preceded by classical assumption tests, with hypothesis testing conducted via t-test at a 95% confidence level. The results indicate that nazhir human resource capacity exerts a significant and positive influence on the effectiveness of productive waqf land management, with a t-count of 7.43 exceeding the t-table value and a coefficient of determination (R²) of 0.71, meaning 71% of management effectiveness variance is explained by nazhir human resource capacity. Among the three dimensions examined, managerial competency emerged as the most dominant contributor, followed by skills and knowledge. These findings confirm that village-level nazhir functioning as competent managerial agents are capable of realizing waqf land's productive potential, with direct implications for SDG 1, SDG 8, and SDG 10 through the generation of sustained community welfare outcomes derived from professionally managed waqf assets.